Rare cell-based liquid biopsy for improved measurement of low-grade chronic inflammation - Schreier, Stefan; Budchart, Prapaphan; Borwornpinyo, Suparerk; Lertsithichai, Panuwat; Triampo, Wannapong (Frontiers in Hematology, 2024)
Objectives and designLow-grade inflammation is a hallmark of chronic diseases. More sensitive tools for chronic low-grade inflammation detection are needed and herein presented as a proof of concept. Heightened sensitivity to inflammation may be achieved by analyzing the compensation mechanisms of hematopoiesis in response to stress. The production of red blood cells and platelets, which are particularly vulnerable to physiological imbalances, are especially important in this context due to their high turnover rates. The compensatory mechanisms involve the production or release of rare immature blood cell types that herein serve as important biomarker targets.MethodsA cell-based liquid biopsy platform, using negative selection, was used to detect circulating rare cells in comprehension, allowing simultaneous analysis of an immature cell panel from one sample. The concentration ranges under physiological conditions for each cell marker were evaluated on a self-reported healthy control cohort and prospectively tested on three individuals undergoing various interventions: one afflicted with early-stage breast cancer, another with atherosclerosis in follow-up, and a third healthy individual with cardiovascular disease risk.ResultsThe approach effectively identified rare cellular abnormalities in asymptomatic individuals who exhibited no abnormalities in their complete blood counts. This condition was designated as silent inflammation (SI). SI was effective in monitoring response to intervention and predicting inflammation state.ConclusionsThe detection of SI proved valuable in aiding inflammation differential diagnosis and for monitoring the response to interventions in all three subjects.